2018
DOI: 10.21472/bjbs.050903
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of lead, chromium and cadmium in tannery effluent using indigenous microorganisms

Abstract: This study investigated the biosorption of lead, chromium and cadmium in tannery effluent using indigenous microorganisms. Bacteria isolated from the tannery effluent were Bacillus subtilis and B. megaterium while fungi isolated were Aspergillus niger and Penicillium sp. The microorganisms were tested for their ability to reduce the concentration of the heavy metals in the tannery effluent using conventional methods. B. megaterium recorded the highest lead reduction (2.13 to 0.03 mg/L), followed by B. subtilis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…The treatments with consortia of organisms reduced the metals more than other treatments which may be attributed to microorganisms living in mixed colonies comprising of different species and genera of organisms where there is synergy of different metabolic activities. Many researchers have reported the higher effectiveness of consortia of microorganisms for bioremediation of heavy metals than single organisms (Kader et al, 2007); Mosa et al, 2016;Abioye et al, 2018) which conforms with the findings of this study where the different combinations of the consortia gave a better result than single treatment procedures.…”
Section: Resultssupporting
confidence: 90%
“…The treatments with consortia of organisms reduced the metals more than other treatments which may be attributed to microorganisms living in mixed colonies comprising of different species and genera of organisms where there is synergy of different metabolic activities. Many researchers have reported the higher effectiveness of consortia of microorganisms for bioremediation of heavy metals than single organisms (Kader et al, 2007); Mosa et al, 2016;Abioye et al, 2018) which conforms with the findings of this study where the different combinations of the consortia gave a better result than single treatment procedures.…”
Section: Resultssupporting
confidence: 90%
“…Abioye and his coworkers [ 123 ] investigated the biosorption of lead (Pb), chromium (Cr), and cadmium (Cd) in tannery effluent using Bacillus subtilis, B. megaterium, Aspergillus niger, and Penicillium sp. B. megaterium recorded the highest lead (Pb) reduction (2.13 to 0.03 mg/L), followed by B .…”
Section: Bioremediation Capacity Of Microorganisms On Heavy Metalsmentioning
confidence: 99%
“…The lipopolysaccharide present in the cell wall contains phosphate and carboxyl groups and phospholides, which are the primary sites of metal ion binding, thereby making biosorption process possible by the microorganism. Abioye et al [23] found that Pseudomonas aeruginosa has been accounted for as effective chromium reducer. In comparative study, on the selective binding of different metals to the cell wall of Pseudomonas species, copper had much more affinity than other heavy metals like nickel and cadmium when evaluated together [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Biosorbents contain some atomic groups that have tendency to sorbates, for example, metal ions. This innovation utilizes different sorts of biomass to expel heavy metals from contaminated environment [19,23].…”
Section: Introductionmentioning
confidence: 99%